Sew home in the kitchen : 18 insulated projects perfect for beginners - Bennett, Abigail American, 1992- (Stash Books, 2020)
"Patterns and instructions to make 18 sewing projects with Insul-Fleece. Includes kitchen items, tote bags, a quilt, and bleacher pad."--